THE EFFECT OF FREE CASH FLOW, PROFITABILITY, LIQUIDITY, AND LEVERAGE ON DIVIDEND POLICY - Wisnu Jati Pramuji; Alien Akmalia (UPT Publikasi Ilmiah UNISBA, 2025)
This study aims to analyze the effect of free cash flow (FCF), profitability (PROF), liquidity (LIQ), and leverage (LEV) on dividend policy. The object of this study is a Manufacturing Company listed on the Indonesia Stock Exchange from 2016 to 2020. In this study using purposive samples with a sample of 140. The analysis method used is the Multiple Linear Regression Analysis method The data analysis technique in this study used EVIEWS 12 software. The F-test result confirms that the regression model is statistically significant, indicating that FCF, ROE, CR, and DER collectively exert a significant influence on dividend policy (DPR). The research results show that the FCF variable has a significant positive effect on the DPR policy, the PROF variable has a significant positive effect on the DPR policy, and the LEV variable has a significant negative effect on the DPR policy. However, the LIQ variable does not have a significant effect on the DPR policy.